New Standards of Senior High School Chinese Textbook in Indonesia: A Case Study of the Vocabulary - Wiratikusuma, Fransiska; Wiratikusuma, Yohana; Wundari, Kumala Dewi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract.  Since the release of the 2013 Curriculum system by the Indonesian Ministry of Education, the vocabulary of Indonesian senior high school Chinese textbooks has constantly been changing. In 2021, The National Language Commission of the Ministry of Education, PRC, released the Chinese Proficiency Grading Standards for International Chinese Language Education (Grading Standard). In the same year, the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia encouraged learning according to students' abilities and provided more expansive space for character development and essential competencies through the 2022 Prototype Curriculum system as an option for all academic units. This curriculum is a system implemented between 2022 and 2024 in the post-COVID-19 learning recovery. Based on the analysis of these new standards, we find out how to adapt to curriculum changes, find out which difficulties arise and how to overcome them. In this study, we use analytic and quantitative research to analyze the teachers' adaptation process to the two new standards in textbook vocabulary. Furthermore, we use the vocabulary statistics of Mandarin textbooks for senior high school, textbook compiling principle-based these two standards and related theory. Through the analysis and statistics of the vocabulary in this textbook, we found that teachers need to adjust some main words in adapting to the two new standards and make a vocabulary selection and supplement to the textbook vocabulary. In addition, to meet the standards of government textbook preparation and meet the expectations of textbook users to understand social life in China through vocabulary to achieve better communication, teachers need teaching resources for textbook vocabulary teaching in this adaptation.Keywords: Indonesian curriculum Prototype Curriculum,Vocabulary learning,Chinese Language new standard, Bahasa Mandarin/汉语 textbook.